The impact of intraoperative “Nerve Monitoring” in a tertiary referral center for thyroid and parathyroid surgery - Princi, Pietro; Gallo, Gaetano; Tempera, Serena Elisa; Umbriano, Antonio; Goglia, Marta; Andreoli, Federica; Nigro, Casimiro (Frontiers in Surgery, 2022)
The most fearsome complication in thyroid surgery is the temporary or definitive recurrent laryngeal nerve (RLN) injury. The aim of our study was to evaluate the impact of intraoperative neuromonitoring (IONM) on postoperative outcomes after thyroid and parathyroid surgery. From October 2014 to February 2016, a total of 80 consecutive patients, with high risk of RLN injuries, underwent thyroid and parathyroid surgery. They were divided in two groups (IONM group and control group), depending on whether neuromonitoring was used or not. We used the Nerve Integrity Monitoring System (NIM)-Response 3.0® (Medtronic Xomed ®). The operation time (p = 0.014). and the length of hospital stay (LOS) (p=0.14) were shorter in the IONM group. Overall mean follow-up was 96.7±14.3 months. The rate of transient RLN palsy was 2.6% in IONM group and 2.5% in the control group (p= not significant). Only one case of definitive RLN injury was reported in control group. No differences were reported between the two groups in terms of temporary or definitive RLN injury. Routine use of IOMN increases the surgery cost, but overall, it leads to long-term cost savings thanks to the reduction of both operating times (106.3 ± 38.7 vs 128.1 ± 39.3, p: 0.01) and LOS (3.2 ± 1.5 vs 3.7 ± 1.5 days, p = not significant). Anatomical visualization of RLN remains the gold standard in thyroid and parathyroid surgery. Nevertheless, IONM is proved to be a valid help without the ambition to replace surgeon's experience.